Public Obedience to Health Protocols during Covid-19 Pandemic in Indonesia: A Perspective from Health Belief Model Theory - Alvania Claresta Sarah Christian (Soshum: Jurnal Sosial dan Humaniora, 2021)
The COVID-19 pandemic is a phenomenon which related to the spread of coronavirus disease 2019. This pandemic that hit the entire world is increasing sharply, including in Indonesia. Several policies have been implemented, one of them is about regulations for doing the COVID-19 health protocols to respond this pandemic. This health protocols aim to ensure the public activities safely during this pandemic. Although these regulations have been implemented in Indonesia, the number of individuals who have been confirmed positive is growing rapidly. This rapid increase in positive cases can be caused by several things. One of them is due to the low obedience of the society towards health protocols during the COVID-19 pandemic. Based on what has been described, this research aims to find out the reasons behind the low obedience of the society towards health protocols during the COVID-19 pandemic by using the theory of the Health Belief Model. Based on the analysis using six components of Health Belief Model, the results of the low obedience of the society towards health protocols during the COVID-19 pandemic are the perception of society about their low potential to be infected of coronavirus disease 2019 by thinking that the disease will appear just like common flu, society doesn’t really understand about the benefits of implementing health protocols, there are obstacles to get the health facilities, lack of government instructions in guiding society on how to act during the pandemic, and the low of society confidence that they are able to reduce the spread of COVID-19 in Indonesia. Therefore, in the future, the government can improve on planning a better way to make society implementing the health protocols during the COVID-19 pandemic. So it can reduce the spread of COVID-19 in Indonesia.